Disharmonization of Wakalah Agreement in Law Number 34 of 2014 and The DSN-MUI Fatwa Number 122/DSN-MUI/II/2018 - Hasan Ali (Faculty of Shariah and Law, UIN Syarif Hidayatullah Jakarta, 2019)
Disharmonization of Wakalah Agreement in Law Number 34 of 2014 and The DSN-MUI Fatwa Number 122/DSN-MUI/II/2018. BPKH as a Hajj financial management institution in Indonesia has an essential role in evolving the Hajj Fund. With the biggest potential of Muslims in the world, Indonesia can administrate hajj finances in a larger scope by investing hajj finances on business lines which has accordance towards sharia principles. In contrast, the wakalah agreement as the basis used between the prospective pilgrims to the BPKH institution is interpreted differently between Law Number 34 of 2014 and the DSN-MUI Fatwa Number 122/DSN-MUI/II/2018 so it causes disharmony in the two laws. Differences in the role interpretation of representatives in both of these invasions have legal consequences in the form of differences in the recipient of responsibilities involving the government and BPKH as the hajj financial manager if they experience investment failure. This study uses qualitative methods with secondary data in the form of legislation, related books, and non-legal materials. The used technique is content analysis with normative juridical research themes that analyze principles and legal systematics.